Cognitive outcomes in trials of two BACE inhibitors in Alzheimer's disease. Issue 11 (13th October 2020) - Wessels, Alette M.; Lines, Christopher; Stern, Robert A.; Kost, James; Voss, Tiffini; Mozley, Lyn Harper; Furtek, Christine; Mukai, Yuki; Aisen, Paul S.; Cummings, Jeffrey L.; Tariot, Pierre N.; Vellas, Bruno; et al.
Abstract: Introduction: The APECS and AMARANTH trials showed that beta‐secretase (BACE) inhibitors verubecestat and lanabecestat failed to slow cognitive and functional decline in individuals with prodromal or early Alzheimer's disease. Here, the performance on secondary and exploratory cognitive measures in both studies is reported. Methods: APECS (verubecestat) and AMARANTH (lanabecestat) were randomized, double‐blind, placebo‐controlled, parallel‐group, 104‐week clinical trials conducted by different sponsors. Measures included the 3‐Domain Composite Cognition Score (CCS‐3D), Repeatable Battery for the Assessment of Neuropsychological Status (RBANS), Letter/Category Fluency, and Digit Symbol Coding. Results: Verubecestat showed worsening on the CCS‐3D Total Score, Episodic Memory, and Attention/Processing Speed domains. Lanabecestat showed worsening on the RBANS Total Score, Immediate Memory, and Visuospatial/Constructional Indexes. Both BACE inhibitors showed worsening on Digit Symbol Coding and improvements on Letter/Category Fluency. Discussion: In both studies, many measures showed treatment‐associated cognitive worsening, whereas verbal fluency tasks showed improvement.